Analysis of Bissu Segeri's Role as an Environmental Communicator - Mariesa Giswandhani; Rahmita Saleh; Amalia Zul Hilmi; Abdul Rahman Saade (International Journal Labs, 2025)
This study investigates the role of the Bissu, a traditional Bugis priestly figure, as an environmental communicator through the Mappalili ritual in Segeri, South Sulawesi. The problem addressed is the declining ecological relevance of traditional rituals amidst rapid modernization and technological changes in agriculture. The objective is to analyze how Bissu communicate environmental values through symbolic practices and assess their effectiveness using environmental leadership indicators: ecological vision, motivating others, exemplary leadership, effective communication, and goal orientation. A qualitative case study approach was employed, involving participatory observation, in-depth interviews, and document analysis. The findings reveal that while the Bissu maintain a strong cultural and symbolic presence in ritual leadership, their influence on practical agricultural and environmental practices has significantly diminished. Their role has shifted from active agents in environmental management to ceremonial figures. Although they promote traditional ecological wisdom, modern agricultural practices and the lack of institutional collaboration limit their communicative effectiveness. This research implies the need to integrate indigenous knowledge with contemporary environmental strategies through policy dialogue and community engagement to preserve cultural identity and promote sustainable development.